(8 intermediate revisions by 2 users not shown)
Line 1: Line 1:
= Practice Question 2, [[ECE438]] Fall 2010, [[User:Mboutin|Prof. Boutin]] =
+
[[Category:problem solving]]
On Computing the z-tramsfprm of a discrete-time signal.
+
 
 +
<center><font size= 4>
 +
'''[[Digital_signal_processing_practice_problems_list|Practice Question on "Digital Signal Processing"]]'''
 +
</font size>
 +
 
 +
Topic: Computing a z-transform
 +
 
 +
</center>
 +
( [[:Category:Problem_solving|Practice Question]] 2, [[ECE438]] Fall 2010, [[User:Mboutin|Prof. Boutin]] )
 
----
 
----
Compute the z-transform of the discrete-time signal  
+
==Question==
 +
<div><span style="color:purple">  Compute the z-transform of the discrete-time signal  
 +
 
 +
<math> x[n]= 4^n \left(u[n+3]-u[n-4] \right) </math>.
  
<math>x[n]= 4^n \left(u[n+3]-u[n-4] \right)</math>.
 
  
 
Note: there are two tricky parts in this problem. Do you know what they are?
 
Note: there are two tricky parts in this problem. Do you know what they are?
----
+
 
 
Post Your answer/questions below.
 
Post Your answer/questions below.
 +
</span></div>
 +
----
 +
== Solution 1 ==
  
<math>x[n] = 4^n u[n+3] - 4^n u[n-4]</math>
+
<span class="texhtml">''x''[''n''] = 4<sup>''n''</sup>''u''[''n'' + 3] 4<sup>''n''</sup>''u''[''n'' − 4]</span>  
  
<math>x[n] = \sum_{n=-\infty}^{\infty} 4^n u[n+3] z^{-n} - \sum_{n=-\infty}^{\infty} 4^n u[n-4] z^{-n}</math>
+
<math>x[n] = \sum_{n=-\infty}^{\infty} 4^n u[n+3] z^{-n} - \sum_{n=-\infty}^{\infty} 4^n u[n-4] z^{-n}</math>  
  
<math>{\color{red}\not}x {\color{red}\not}[n]  {\color{red}X(z)} = \sum_{n=3}^{\infty} 4^n z^{-n} - \sum_{n=-\infty}^{4} 4^n z^{-n}</math>
+
<math>{\color{red}\not}x {\color{red}\not}[n]  {\color{red}X(z)} = \sum_{n=3}^{\infty} 4^n z^{-n} - \sum_{n=-\infty}^{4} 4^n z^{-n}</math>  
  
<math>{\color{red}\not}x {\color{red}\not}[n]  {\color{red}X(z)}= \sum_{n=0}^{\infty} (\frac{4}{z})^n - 85 - \sum_{n=4}^{\infty} (\frac{4}{z})^n</math>
+
<math>{\color{red}\not}x {\color{red}\not}[n]  {\color{red}X(z)}= \sum_{n=0}^{\infty} (\frac{4}{z})^n - 1 - 4^1z^{-1} - 4^2z^{-2} - 4^3z^{-3} - \sum_{n=4}^{\infty} (\frac{4}{z})^n</math>  
  
this is the mistake I made on my exam - could you please clarify my work, professor?
+
this is the mistake I made on my exam - could you please clarify my work, professor?  
*Certainly! This is a very common mistake: splitting a sum that converges for most z's  into two sums that diverge for most z's.  The key is to notice that the first sum above has a finite number of  terms: so convergence of the entire sum is guaranteed, unless one (or more) of the terms of the sum diverge (for example, 1/z diverges when z=0). Observe that, by splitting the sum this way,  you get an empty ROC. The correct ROC for this z-transform is actually all the finite complex plane except zero. -pm
+
  
*Another thing I see is the manipulation of the sum with negative indices, namely :
+
*<div><span style="color:green"> Certainly! This is a very common mistake: splitting a sum that converges for most z's  into two sums that diverge for most z's.  The key is to notice that the first sum above has a finite number of  terms: so convergence of the entire sum is guaranteed, unless one (or more) of the terms of the sum diverge (for example, 1/z diverges when z=0). Observe that, by splitting the sum this way,  you get an empty ROC. The correct ROC for this z-transform is actually all the finite complex plane except zero. -pm</span></div>
:<math>\sum_{n=-\infty}^{4} 4^n z^{-n } =  \sum_{n=4}^{\infty}(\frac{4}{z})^n </math>
+
 
:which is incorrect. The correct way to manipulate it is the following:
+
*<div><span style="color:green">Another thing I see is the manipulation of the sum with negative indices, namely&nbsp;:
 +
</span></div>
 +
 
 +
:<math>{\color{green}\sum_{n=-\infty}^{4} 4^n z^{-n } =  \sum_{n=4}^{\infty}(\frac{4}{z})^n }</math>  
 +
:which is incorrect. The correct way to manipulate it is the following:  
 
:<math>
 
:<math>
 
\begin{align}
 
\begin{align}
Line 29: Line 45:
 
         &=  \sum_{k=-4}^{\infty} 4^{-k} z^{k }  \text{ (since the order of the terms in the sum does not matter)}, \\
 
         &=  \sum_{k=-4}^{\infty} 4^{-k} z^{k }  \text{ (since the order of the terms in the sum does not matter)}, \\
 
&= 4^{4}z^{-4}+4^{3}z^{-3}+4^{2}z^{-2}+4^{1}z^{-1}+ \sum_{k=0}^{\infty} 4^{-k} z^{k }
 
&= 4^{4}z^{-4}+4^{3}z^{-3}+4^{2}z^{-2}+4^{1}z^{-1}+ \sum_{k=0}^{\infty} 4^{-k} z^{k }
\end{align}
+
\end{align}</math>  
</math>  
+
:<span style="color:green">Hope that helps! -pm  
:Hope that helps! -pm
+
</span>
 +
 
 +
 
 +
 
 +
<math>X(z) =\sum_{n=0}^{\infty} (\frac{4}{z})^n - 1 - 4z - 4^2z^{2} - 4^3z^{3} - (4^{4}z^{-4}+4^{3}z^{-3}+4^{2}z^{-2}+4^{1}z^{-1}+ \sum_{k=0}^{\infty} 4^{-k} z^{k })</math>
 +
 
 +
::Or better yet:
 +
:::<math>X(z) =\sum_{n=-3}^{3} (\frac{4}{z})^n</math> -pm
 +
 
 +
<br>
 +
 
 
----
 
----
  
*Answer/question
+
*Answer/question  
*Answer/question
+
 
*Answer/question
+
----
 +
<div><span style="color:blue">  Note: although the signal given looks very similar to
 +
 
 +
<math>{\color{blue} x_1[n]= 4^n u[n+3]- 2^n u[n-4]  }</math>.
 +
 
 +
and to
 +
 
 +
<math>{\color{blue} x_2[n]= 4^n u[n+3]- 2^n u[-n-4]  }</math>.
 +
 
 +
the computation of the z-transform is very different. -pm
 +
 
 +
</span></div>
 +
----
 +
*Comment/answer/question  
 +
*Comment/answer/question
 
----
 
----
[[Practice_question_1_eECE439F10|Previous practice problem]]
 
  
[[Practice_Question_3_ECE439F10|Next practice problem]]
+
[[Practice question 1 eECE439F10|Previous practice problem]]  
  
 +
[[Practice Question 3 ECE439F10|Next practice problem]]
  
[[2010 Fall ECE 438 Boutin|Back to 2010 Fall ECE 438 Boutin]]  
+
<br> [[2010 Fall ECE 438 Boutin|Back to 2010 Fall ECE 438 Boutin]]  
  
 
[[Category:2010_Fall_ECE_438_Boutin]]
 
[[Category:2010_Fall_ECE_438_Boutin]]
 +
[[Category:z-transform]]

Latest revision as of 12:48, 26 November 2013


Practice Question on "Digital Signal Processing"

Topic: Computing a z-transform

( Practice Question 2, ECE438 Fall 2010, Prof. Boutin )


Question

Compute the z-transform of the discrete-time signal

$ x[n]= 4^n \left(u[n+3]-u[n-4] \right) $.


Note: there are two tricky parts in this problem. Do you know what they are?

Post Your answer/questions below.


Solution 1

x[n] = 4nu[n + 3] − 4nu[n − 4]

$ x[n] = \sum_{n=-\infty}^{\infty} 4^n u[n+3] z^{-n} - \sum_{n=-\infty}^{\infty} 4^n u[n-4] z^{-n} $

$ {\color{red}\not}x {\color{red}\not}[n] {\color{red}X(z)} = \sum_{n=3}^{\infty} 4^n z^{-n} - \sum_{n=-\infty}^{4} 4^n z^{-n} $

$ {\color{red}\not}x {\color{red}\not}[n] {\color{red}X(z)}= \sum_{n=0}^{\infty} (\frac{4}{z})^n - 1 - 4^1z^{-1} - 4^2z^{-2} - 4^3z^{-3} - \sum_{n=4}^{\infty} (\frac{4}{z})^n $

this is the mistake I made on my exam - could you please clarify my work, professor?

  • Certainly! This is a very common mistake: splitting a sum that converges for most z's into two sums that diverge for most z's. The key is to notice that the first sum above has a finite number of terms: so convergence of the entire sum is guaranteed, unless one (or more) of the terms of the sum diverge (for example, 1/z diverges when z=0). Observe that, by splitting the sum this way, you get an empty ROC. The correct ROC for this z-transform is actually all the finite complex plane except zero. -pm
  • Another thing I see is the manipulation of the sum with negative indices, namely :
$ {\color{green}\sum_{n=-\infty}^{4} 4^n z^{-n } = \sum_{n=4}^{\infty}(\frac{4}{z})^n } $
which is incorrect. The correct way to manipulate it is the following:
$ \begin{align} \sum_{n=-\infty}^{4} 4^n z^{-n } &= \sum_{k=\infty}^{-4} 4^{-k} z^{k } \text{ (letting }k=-n), \\ &= \sum_{k=-4}^{\infty} 4^{-k} z^{k } \text{ (since the order of the terms in the sum does not matter)}, \\ &= 4^{4}z^{-4}+4^{3}z^{-3}+4^{2}z^{-2}+4^{1}z^{-1}+ \sum_{k=0}^{\infty} 4^{-k} z^{k } \end{align} $
Hope that helps! -pm


$ X(z) =\sum_{n=0}^{\infty} (\frac{4}{z})^n - 1 - 4z - 4^2z^{2} - 4^3z^{3} - (4^{4}z^{-4}+4^{3}z^{-3}+4^{2}z^{-2}+4^{1}z^{-1}+ \sum_{k=0}^{\infty} 4^{-k} z^{k }) $

Or better yet:
$ X(z) =\sum_{n=-3}^{3} (\frac{4}{z})^n $ -pm



  • Answer/question

Note: although the signal given looks very similar to

$ {\color{blue} x_1[n]= 4^n u[n+3]- 2^n u[n-4] } $.

and to

$ {\color{blue} x_2[n]= 4^n u[n+3]- 2^n u[-n-4] } $.

the computation of the z-transform is very different. -pm


  • Comment/answer/question
  • Comment/answer/question

Previous practice problem

Next practice problem


Back to 2010 Fall ECE 438 Boutin

Alumni Liaison

Ph.D. 2007, working on developing cool imaging technologies for digital cameras, camera phones, and video surveillance cameras.

Buyue Zhang